Mindfulness-Based Functional Therapy: a preliminary open trial of an integrated model of care for people with persistent low back pain - Schütze, Robert; Slater, Helen; O'Sullivan, Peter; Thornton, Jennifer; Finlay-Jones, Amy; Rees, Clare S. (Frontiers in Psychology, 2014)
Objectives: This pilot study investigated the feasibility and clinical utility of implementing a novel, evidence-informed, interdisciplinary group intervention – Mindfulness Based Functional Therapy (MBFT) – for the management of persistent low back pain (LBP) in primary care. MBFT aimed to improve physical and psychological functioning in patients with persistent LBP. Design: A single-group repeated measures design was utilized to gather data about feasibility, effect sizes, clinically significant changes and patient satisfaction. Setting: A community sample of 16 adults (75% female), mean (SD) age 47.00 (9.12) years (range 26-65 years), with mean (SD) LBP duration of 8.00 (9.00) years participated, using a simulated primary care setting at Curtin University in Australia. Intervention: MBFT is an 8-week group intervention co-facilitated by psychology and physiotherapy disciplines. Content includes: mindfulness meditation training, cognitive-functional physiotherapeutic movement retraining, pain education, and group support. Main outcome measures: Several validated self-report measures were used to assess functional disability, emotional functioning, mindfulness, pain catastrophizing, health-related quality of life at baseline, post-intervention, and 6 months follow-up. Results: Adherence and satisfaction was high, with 85% of participants highly satisfied with MBFT. Clinical significance analysis and effect size estimates showed improvements in a number of variables, including pain catastrophizing, physical functioning, role limitations due to physical condition, and depression, although these may have occurred due to non-intervention effects. Conclusions: MBFT is feasible to implement in primary care. Preliminary findings suggest that a randomized controlled trial is warranted to investigate its efficacy in improving physical and emotional functioning in people with disabling persistent LBP.